Multi-dimensional quasitoeplitz Markov chains. (1999) - Dudin, Alexander N.; Klimenok, Valentina I.
Abstract : This paper deals with multi-dimensional quasitoeplitz Markov chains. We establish a sufficient equilibrium condition and derive a functional matrix equation for the corresponding vector-generating function, whose solution is given algorithmically. The results are demonstrated in the form of examples and applications in queues with BMAP-input, which operate in synchronous random environment.